2012
DOI: 10.1111/j.1365-2966.2012.20967.x
|View full text |Cite
|
Sign up to set email alerts
|

On the accumulation of planetesimals near disc gaps created by protoplanets

Abstract: We have performed three‐dimensional two‐fluid (gas–dust) hydrodynamical models of circumstellar discs with embedded protoplanets (3–333 M⊕) and small solid bodies (radii 10 cm to 10 m). We find that high‐mass planets (≳ Saturn mass) open sufficiently deep gaps in the gas disc such that the density maximum at the outer edge of the gap can very efficiently trap metre‐sized solid bodies. This allows the accumulation of solids at the outer edge of the gap as solids from large radii spiral inwards to the trapping r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
80
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(86 citation statements)
references
References 71 publications
(140 reference statements)
6
80
0
Order By: Relevance
“…Furthermore, as observed in Ayliffe et al (2012) there is a strong correlation between particle size and particle gap, where the most coupled particles reach regions closer to the planet and can be accreted by the planet or can migrate to the inner disk, while less coupled particles are effectively filtrated by the planet.…”
Section: Comparison With Previous Workmentioning
confidence: 84%
“…Furthermore, as observed in Ayliffe et al (2012) there is a strong correlation between particle size and particle gap, where the most coupled particles reach regions closer to the planet and can be accreted by the planet or can migrate to the inner disk, while less coupled particles are effectively filtrated by the planet.…”
Section: Comparison With Previous Workmentioning
confidence: 84%
“…It is therefore necessary to take a critical look at the fidelity of the method. While many code comparisons exist in the case of purely gaseous discs (Meru & Bate 2011, 2012Paardekooper, Baruteau & Meru 2011), the dust implementation has been hitherto untested in this context (although, for studies of dust in general see Laibe & Price 2011, 2012Ayliffe et al 2012;Lorén-Aguilar & Bate 2014).…”
Section: Discussionmentioning
confidence: 99%
“…They found that using the gas smoothing length partially resolves the issue, since the gas has lower density and a larger smoothing length. We suspect that both error in the dust density and requirement that the gas is resolved on length scales present in the dust distribution are important for resolving the issue (Ayliffe et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Another approach is to model the dust population as a continuous, pressureless fluid (Barrière-Fouchet et al 2005;Paardekooper & Mellema 2006;Ayliffe et al 2012;Meheut et al 2012;Fu et al 2014;Lorén-Aguilar & Bate 2014;Surville et al 2016). The hydrodynamic equations are evolved for two fluids: the gas and dust, with density and velocity r g , v g and r d , v d , respectively.…”
Section: Introductionmentioning
confidence: 99%